IMPLEMENTASI PENGATURAN PROXY SERVER MENGGUNAKAN SERVICE SQUID PADA SISTEM OPERASI LINUX - Esron Rikardo Nainggolan (Jurnal Techno Nusa Mandiri, 2015)
Network operating system is an operation which is used to coordinate activities of multiple computers in a network, the network operating system development related with open source operating system development that would have much effect on treatment patterns in information technology. One of the server network operating system services quite effects in the handling of information technology is a proxy server that provides dial computer (Internet programs such as browsers, download managers and other) to the internet. In the manufacture of proxy servers, the author uses the Linux operating system with the service squid as a proxy application. Generally, a proxy server is very useful in the management of information technology, namely in terms of speeding up access to the Internet and can be used to filter unwanted content.